PENGEMBANGAN MODUL BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS) PADA MATERI SIFAT KOLIGATIF LARUTAN - Fazlina Arisya; Sri Haryati; Betty Holiwarni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2021)
This research is aimed to develop modules based on STEM on the colligative properties of class XII SMA / MA. This type of research is research and development (R & D) with a 4D model that includes the phases of Define, Design, Develop and Diseminate. The developed research was carried out until the development phase (develop) in the form of one-on-one trials, and trials were limited to teachers. This research was fully conducted at FKIP Riau University, MAN 1 Pekanbaru and Cendana Pekanbaru High School. The data analysis technique used in the study was descriptive statistical analysis, carried out by calculating the score obtained at the time of validation. The evaluation of module feasibility aspects by the validator team in the form of content eligibility, STEM characteristics, linguistic, presentation, and graphic characteristics have scores of 80%, 87.5%, 80.205%, 90.625%, and 91.25%, respectively. Overall the average score of the validation modules of the STEM-based solution was 85.916% included in the validity eligibility criteria, meaning that the module developed was eligible to be tested on a limited basis whereas the teacher's response to the module getting a percentage of 92.1% in good criteria.